Pengaruh Kepemimpinan terhadap Kinerja Pegawai Negeri Sipil pada Kantor Wilayah Kementrian Agama Provinsi Riau - Jeli Nata Liyas; Ferisca Nur Widyanti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The purpose of this study was to determine the effect of leadership on the performance of regional office employees in the Ministry of Riau province. The population used in this study was 181 people. The sampling method uses the slovin formula in analyzing data obtained from research objects using quantitative analysis and the number of respondents is 65 people. The results of data processing through SPSS data analysis using the simple linear regression method with the results Y = 18.184 + 0.867x, from the t test there is a t count of 6.374 it can be seen that the value of t count > t table (6.374 > 1.99834) means that leadership has a significant effect on performance employees at the Regional Office of the Ministry of Religion of Riau Province. it can be seen that the R square value is 0.392, this means that the leadership variable (X) contributes or contributes to the dependent variable where the leadership is 0.392 or 39.2% while the remaining 60.8% is influenced by other variables not examined in this study. this research.